Safety evaluation of timber structures through probabilistic analysis - Sousa, Hélder S. (2010)
This work presents a procedure for the use of probabilistic modelling techniques in the assessment of safety parameters of existing timber structures, when influenced by two types of actions. The parameters of the models have been defined as probabilistic variables, and Monte Carlo simulation technique was taken into account for safety evaluation. The case study here examined concerns four king post trusses on which a safety evaluation method was conducted to determine a target reliability index. Since the structures presented a high level of deterioration, a model considering the variation of the residual cross-section and the influence of environment in resistance was taken into account. Time dependent deterioration models have also been considered. With the results given by the different used models, it was possible to obtain probabilities of failure and respective reliability indices, as well as time evolution deterioration curves for a deteriorated historical structure.